Is Convergence a Realistic Prospect for the Transition Economics - Haynes, Michael; Husan, Rumy (Ekonomika, 2001)
To make a proper evaluation of transition it is necessary to appreciate the reasons for slow convergence in the former Soviet bloc as well as many other of the world’s poorer economies. One of the most important reasons lie in the long run spatial inequalities caused by the historical development of the world economy. Estimates of output per capita for the year 1800 already reflect the economic gap between the richest and the poorest regions of Europe the latter including the area of modem Eastern Europe. The nature of the transition crisis can be considered from other four points: the restructuring process compressed into half a decade which forced these economies downward in the international division of labour; the fact that the developing economies are chasing a moving target - the advanced economies that have continuous)y grown; the transition process started in a period of general slowdown in the world economy and finally the recovery results in divergence in many transition economies. There are long run development problems in Eastern Europe and Russia as well as on the global scale. These problems cannot be solved by any regime or policy since they are rooted in the historical development of the world economy. And although the people of the regions are promised a more prosperous future in absolute terms, the facts do not promuch evidence of it.